Mineralogical characterization by rare earths in mineral deposits of central Peru - Quiñones Lavado, Lourdes Janet (2016)
The main objective of this study was the rare earth mineralogical characterization of samples from mineral deposits in central Peru. To determine the mineralogical composition, the light microscopy technique was used by means of a reflected light polarization microscope and for the analysis of the rare earth bearing minerals, the mass spectrometry method (ICP-MS) technique, which is used for the study of materials loose or rare earths. The microscopic analysis of the samples from the mineral deposits of Milpo (Pilar Mine), Chungar and Mina Raúl determined the mineralogical composition made up of mineral species, such as pyrite, sphalerite, galena, chalcopyrite, marcasite, magnetite, pyrrhotite, goethite, tetrahedrite, bornita, covelita and bargains. The study of the samples applying the ICP MS technique confirmed the presence of rare earth elements such as cerium (ce), dysprosium (dy), erbium (er), europium (eu), gadolinium (gd), holfnium (ho ), lanthanum, lutetium (lu), neodymium (nd), praseodymium (pr), samarium (sm), terbium (tb), tulium (th), (tm), uranium (u) yttrium (y) and ytterbium (yb ) that they are rare earth elements of economic interest, said result is reported in a qualitative and quantitative way.